STRATEGI INTERNALISASI NILAI-NILAI ISLAM MODERAT MELALUI KURIKULUM PAI DALAM MEWUJUDKAN LINGKUNGAN BELAJAR TOLERAN DI SEKOLAH MULTIRELIGIUS (STUDI DI SMP 1 BAURENO) - Andika Darmawan; Ali Ahmad Yenuri (Journal Multicultural of Islamic Education, 2026)
Religious diversity within the school environment is a social reality that requires a wise and contextual educational approach in order to create a conducive, inclusive, and harmonious learning climate. In multireligious schools such as SMPN 1 Baureno, Islamic Religious Education (PAI) plays a crucial role in instilling moderate Islamic values as a foundation for developing tolerant attitudes, without neglecting the strengthening of students’ religious identity. This study aims to examine strategies for internalizing moderate Islamic values through the PAI curriculum and to analyze the efforts undertaken by the school to maintain the consistency of students’ religious identity amid intensive interfaith interactions. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation, and subsequently analyzed using the interactive model proposed by Miles and Huberman. The findings indicate that the internalization of moderate Islamic values is implemented through the integration of these values into instructional planning, the application of dialogical and collaborative learning strategies, educators’ role modeling, and the reinforcement of school culture through religious activities and positive habituation. Meanwhile, the strengthening of students’ religious identity is carried out through the deepening of religious creed (aqidah), the provision of worship facilities in accordance with each belief, counseling assistance, and collaboration among the school, parents, and the surrounding community. The findings of this study emphasize that the success of religious moderation education in multireligious schools is largely determined by the school’s ability to maintain a balance between fostering tolerance and strengthening religious commitment. Theoretically, this study contributes to the development of religious moderation studies in the field of education, while practically it offers recommendations for the development of a PAI curriculum oriented toward the formation of religious, moderate, and tolerant character.